Pengaruh Program Kurassaki (Kurangi Sampah Sekolah Kita) Terhadap Kebersihan Sekolah Pada Siswa di SDN Kutabaru I Kabupaten Tangerang: The Effect Of Kurassaki (Reduce Our School Waste) Program On School Hygiene In Students At Kutabaru I Elementary School Tangerang District - Novellia Amanda; Reksa Adya Pribadi; Lukman Nulhakim (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This study aims to determine the effect of the kurassaki (reduce our school waste) programme on school hygiene in students at SDN Kutabaru I, Tangerang Regency. The research approach used is quantitative with correlational method. The data in this study were obtained through distributing questionnaires to respondents and analysed using simple regression tests and correlation tests. The location of this research was SDN Kutabaru I, Tangerang Regency. The population in this study were all students at SDN Kutabaru I, Tangerang Regency. The sampling technique in this study used random sampling technique and the number of samples was determined using the Solvin formula with a significance level of 5% so that the number of samples in this study was 264 respondents. The results of simple regression testing obtained Fcount 81.71> Ftable 1.22 with the equation Y = 33.79 + 0.53X. This shows that there is a significant influence between the kurassaki (reduce our school waste) programme on school hygiene. Meanwhile, the results of correlation testing obtained an rxy value of 0.48 which is based on the table of criteria for determining the amount of correlation coefficient is at the